(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
Relations between South Sudan and China are not a new phenomenon. However, since 2011 they have been steadily growing in terms of trade and investments, cultural exchanges, development and humanitarian aid. The breakout of the civil war in December 2013 has contributed to this trend. Amidst the disenchantment of traditional Western partners of South Sudan, massive shifts of aid flows from development to humanitarian response, and the flight of foreign capitals scared by the war, not only did China keep its presence in the country, it also took a more active stance by sending its first combat troops ever in the framework of the UN Mission, and engaging in the peace negotiations. What consequences has China’s growing presence had on South Sudan’s capacity of determining its own political agenda? This article argues that it has provided an opportunity of expanding the space for agency of the South Sudanese governing elite to make choices in opposition to the requests of traditional donors. At the same time, since relations with China are bound to pragmatic considerations from both sides, there is evidence that China’s will to partner with the country is only as strong as the potential benefits accruing from this partnership.